Exogenous Gibberellins and Auxins Promote Crown Bud Regeneration and Influence Endogenous Hormone Changes in Alfalfa - Haiyan Yue; Qunce Sun; Shuzhen Zhang; Youping An; Xianwei Peng; Binghan Wen; Xingyu Ge; Yuxiang Wang (Plants)
Alfalfa (Medicago sativa L.) is a globally significant forage crop with notable economic value. Gibberellins (GA3) promote dormancy breaking and early germination whereas auxins (IAA) predominantly influence bud regeneration. This study investigated the effects of exogenous gibberellins and indole acetic acid on the regeneration and biomass of crown buds in two alfalfa varieties with different dormancy levels. The experiment involved five concentrations each of gibberellins (0 mg/L, 10 mg/L, 20 mg/L, 30 mg/L, and 40 mg/L) and auxins (0 mg/L, 5 mg/L, 10 mg/L, 15 mg/L, and 20 mg/L). The results indicated that both exogenous gibberellins and auxins significantly increased the endogenous levels of these hormones in the crown buds, while decreasing abscisic acid (ABA) levels. There was also a significant increase in sugar and total nitrogen content in the buds. Treatments with exogenous gibberellins enhanced the number of crown buds and the aboveground biomass per plant, with the best results at 30 mg/L. Auxin treatments showed the largest increase in aboveground biomass per plant at 15 mg/L. In summary, 30 mg/L gibberellins or 15 mg/L auxins is recommended as the optimal spraying concentration. This research provides practical evidence for the regulation of exogenous growth regulators in alfalfa cultivation.